Professor Eduard Anatoliyovych Derkachov (to 80-th birthday) - Rublevska, N. I.; Shevchenko, O A; Biletska, E. M. (Medicni Perspektivi, 2019)
Professor Eduard Anatoliyovych Derkachov (to 80-th birthday)